The effects of resonant magnetic perturbations on fast ion confinement in the Mega Amp Spherical Tokamak. (15th May 2015) - McClements, K G; Akers, R J; Boeglin, W U; Cecconello, M; Keeling, D; Jones, O M; Kirk, A; Klimek, I; Perez, R V; Shinohara, K; Tani, K
Abstract: The effects of resonant magnetic perturbations (RMPs) on the confinement of energetic (neutral beam) ions in the Mega Amp Spherical Tokamak (MAST) are assessed experimentally using measurements of neutrons, fusion protons and fast ion D α (FIDA) light emission. In single null-diverted (SND) MAST pulses with relatively low plasma current (400 kA), the total neutron emission dropped by approximately a factor of two when RMPs with toroidal mode number n = 3 were applied. The measured neutron rate during RMPs was much lower than that calculated using the TRANSP plasma simulation code, even when non-classical (but axisymmetric) ad hoc fast ion transport was taken into account in the latter. Sharp drops in spatially-resolved neutron rates, fusion proton rates and FIDA emission were also observed. First principles-based simulations of RMP-induced fast ion transport in MAST, using the F3D-OFMC code, show similar losses for two alternative representations of the MAST first wall, with and without full orbit effects taken into account; for n = 6 RMPs in a 600 kA plasma, the additional loss of beam power due to the RMPs was found in the simulations to be approximately 11%.